Votingon the "Optimal" Size of Government - Olters, Jan-Peter (IMF Working Papers; Working Paper ;, 2000)
Viewing fiscal policies as the outcome of democratically resolved conflicts of households over public goods and taxes, the 'economic model of politics' proposes a public choice approach, which does not rely on social welfare functions. With it, a country's overall budget can be derived endogenously, electoral fluctuations explained on the basis of changes to the individuals' income and wealth, and political behavior described in terms of the individuals' decisions regarding votes, abstentions, and party membership. The model suggests that a country's wealth distribution is a crucial variable affecting its economic stability and the government's size relative to output.